A novel recovery loop for reducing greenhouse gas emission: Simultaneous production of syngas and pure hydrogen in a membrane reformer. (June 2020) - Parvasi, P.; Jokar, S.M.; Shamseddini, A.; Babapoor, A.; Mirzaie, F.; Abbasfard, H.; Basile, A.
Abstract: In this work, a novel loop is designed for simultaneous production of pure hydrogen and synthesis gas (syngas) from a domestic refinery purge gas. The purge gases are the combination of flare gas (consist mainly of methane) and high-temperature flue gas (containing CO2 and steam). The proposed loop including three main parts: 1) flare gas desulfurization unit; 2) CO2 and steam recovery unit and, 3) a membrane reformer for combined dry-steam reforming of methane, heating with high-temperature flue gas. The hazardous hot gases convert to valuable products instead of discharging to the atmosphere. A steady-state one-dimensional model is used to predict the loop performance. The results show that 55.5% of methane conversion can be achieved from the purge gases consisting of 797 kmol/h flare gas and 17, 200 kmol/h flue gas. The proposed process can produce 338 kmol/h of pure hydrogen and 1, 209 kmol/h of syngas. In addition, the effects of purge gas properties and process modifications on the loop performance were investigated. The method presented in this work is a promising alternative to reduce purge gas released to the atmosphere from industrial plants. This can result in a significant reduction in CO2 emissions that causes global warming. Graphical abstract: Image 108965 Highlights: A novel loop designed to produce pure hydrogen and syngas from refinery purge gases. A combine dry-steam reforming of flare gas takes place in a membrane reformer. The proposed loop produces 338 kmol/h of pure hydrogen and 1, 209 kmol/h of syngas. The waste heat, CH4 and CO2 emissions from refinery lowered significantly.